2019
DOI: 10.2135/cropsci2018.05.0343
|View full text |Cite
|
Sign up to set email alerts
|

Shading and Nitrogen Effects on Cotton Earliness Assessed by Boll Yield Distribution

Abstract: Shading and N fertilization affect fruit distribution in cotton (Gossypium hirsutum L.), but there is no detailed information on earliness of crop maturity according to phenological development. The aim of this work was to evaluate the effect of shading at early flowering and N top‐dressing rates on relative cotton earliness using plant mapping. Field experiments were conducted in Itapeva (16 d of shading; and 0, 60, 120, and 180 kg N ha−1) and Chapadão do Sul (17 d of shading; 0, 80, and 160 kg N ha−1; and ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 37 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…The cotton yield is determined by a few key factors, including species and genetics [1], soil [2] and nutrition [3,4] conditions, weather [5], irrigation [6,7], and management events [8]. Specifically, cotton is a perennial warm-season crop that requires a long growing period.…”
Section: Introductionmentioning
confidence: 99%
“…The cotton yield is determined by a few key factors, including species and genetics [1], soil [2] and nutrition [3,4] conditions, weather [5], irrigation [6,7], and management events [8]. Specifically, cotton is a perennial warm-season crop that requires a long growing period.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were obtained in this study. Studies have shown that either insufficient or excessive nitrogen application can lead to decreased yield ( Raphael et al., 2019 ; Hassanzadehdelouei et al., 2022 ). The results of this study demonstrate that amount of nitrogen application significantly affects cotton yield and quality.…”
Section: Discussionmentioning
confidence: 99%
“…It determines plant growth, fruiting and seed cotton yield by regulates photosynthesis and other physiological processes [13]. Cotton earliness has also been found affected by N levels [14]. Nitrogen application increase yield and yield related traits of cotton [15].…”
Section: Introductionmentioning
confidence: 99%